Students Ability to Rewrite The Retelling Descriptive Text (International Journal of Business and Information Technology, 2023)
Retelling Story is post reading and post listening, a story in which readers and listeners tell what they remember from what they have read or listened to. Descriptive is a written English text in which the writer describes an object. Based on the above background, the writer limits the problem on the students’ ability to rewrite the retelling descriptive text at Mts Zun Nuraini. This research use technique of collecting data Questionnaires, this questionnaire about some question for the respondents dealing with the factors influence the students can't understand to rewrite the retelling descriptive text. So from the data above the writer concludes that the ability of students depend on stimulator from the internal factors that can build their motivation in learning, especially in learning English grammar. Based on the research data in previous chapter, it can be conclude that the students error to rewrite the retelling descriptive text at eighth year students of Mts Zun Nuraini depend on stimulate from the internal factors. This can be seen on the result of the questionnaire conducted by the writer.